Peningkatan Hasil Belajar Siswa dalam Pembelajaran IPS dengan Pendekatan CTL di Kelas IV Sekolah Dasar - Fitri, Restia; S, Farida; Yunisrul, Yunisrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The research aimed at improving students’ science learning outcomes by using Contextual Teaching and Learning at the four grade. The research was conducted at SDN 48 Kuranji Kota Padang. The subjects of the research were teachers and 28 four grade students. The research findings showed that there was such improvement. In cycle I obtained the average percentage of student learning outcomes 46.43 and in cycle II is 92.86. Thus, Contextual Teaching and Learning approach can improve student learning outcomes in learning Science in class IV SDN 48 Kuranji Kota Padang.  Key Word:  Result Study, Outcomes of Social Science , Approach, Contextual Teaching and Learning